Introduction to threshold concepts in business education. Issue 5 (13th June 2016) - Bajada, Christopher; Trayler, Rowan
Abstract : Purpose: – To introduce to the special issues on threshold concepts in business education. Design/methodology/approach: – Provides an overview of the various papers comprising this special issue. Findings: – There are no specific findings in this paper as its purpose is to introduce the selected papers in this special issue. Originality/value: – Editorial.